Crosstalk between keratinocytes and neutrophils shapes skin immunity against S. aureus infection - Focken, Jule; Schittek, Birgit (Frontiers in Immunology, 2024)
Staphylococcus aureus infection of the skin leads to a rapid initial innate immune response with keratinocytes in the epidermis as the initial sensors. Polymorphonuclear neutrophils (PMNs) are the first innate immune cells to infiltrate infection sites where they provide an effective first-line of defense. Previous work of our group showed that in inflamed skin a crosstalk between PMNs and keratinocytes enhances S. aureus skin colonization. Here, we show that co-culture of PMNs with primary human keratinocytes (PHKs) induces activation and degranulation of PMNs and significantly enhances their lifespan compared to PMN cultivation alone by an IL-8 mediated mechanism and, furthermore, primes PMNs for enhanced activity after S. aureus infection. The prolonged incubation with PMNs also induces inflammatory responses in PHKs which are further exacerbated in the presence of S. aureus and induces further PMN recruitment thus fueling skin inflammation Interestingly, infection of PHKs with the skin commensal S. epidermidis reduces the inflammatory effect of PMNs in the skin and exhibit an anti-inflammatory effect. Our data indicate that skin infiltrating PMNs and keratinocytes influence each other in such a way to enhance skin inflammation and that commensal bacteria are able to reduce the inflammatory effect.